Rare bird documentation form for Northern Goshawk at George Wyth State Park, 1985 - Moore, Francis L.et al (1985)
Rare bird documentation form for a Northern Goshawk at George Wyth State Park in Black Hawk County, IA on November 21, 1985. Epson - sheet feed